The Effects of Equity Crowdfunding and Business Partnership Relationships on Business Performance: A Study on MSMEs Registered in Santara - Dewi Kurnia Safitri; Maria Rio Rita (Universitas Proklamasi 45, 2022)
This study aims to examine the effects of equity crowdfunding and business partnership relationships on the performance of micro, small, and medium enterprises (MSMEs). To the best of the researcher’s knowledge, there are still relatively few studies that discuss the relationship between these variables and business performance. These findings can add a reference to studies in the field of entrepreneurial finance, especially regarding equity crowdfunding for MSMEs. The analysis used was a multiple linear regression approach which was processed with SPSS 26.0 software. The sampling technique used a purposive sampling method. The data was obtained through the distribution of online questionnaires to 83 MSMEs registered in an application that is active in the fintech equity crowdfunding field called Santara. The study proved that equity crowdfunding has a significant positive effect on the performance of MSMEs, and the business partnership relationship has a significant positive effect on the performance of MSMEs. Equity crowdfunding is an alternative for MSMEs to obtain business capital other than bank loans. In addition, establishing a partnership will have a positive impact on business progress if it is carried out with the principle of mutual strengthening, needs, and benefits between parties.